2019
DOI: 10.1097/cm9.0000000000000279
|View full text |Cite
|
Sign up to set email alerts
|

Early-life stress alters sleep structure and the excitatory-inhibitory balance in the nucleus accumbens in aged mice

Abstract: Background: Exposure to adverse experiences in early life may profoundly reshape the neurodevelopmental trajectories of the brain and lead to long-lasting behavioral and neural alterations. One deleterious effect of early-life stress that manifests in later life is sleep disturbance, but this has not been examined in aged mice and the underlying neural mechanisms remain unknown. Considering the important role of the nucleus accumbens (NAc) in the sleep-wake regulation, this study aimed to assess t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 35 publications
(44 reference statements)
2
5
0
Order By: Relevance
“…Conversely, activation and inhibition of VTA GABA neurons was found to promote sleep and wakefulness, respectively (Chowdhury et al, 2019; Yu et al, 2019), in part due to the impact of these manipulations on the activity of VTA dopamine neurons. Because the VTA is the major source of dopaminergic innervation of the NAc, these findings are consistent with multiple additional lines of evidence implicating the NAc in the regulation of arousal and sleep (Barik and de Beaurepaire, 2005; Lazarus et al, 2011; Lena et al, 2005; Luo et al, 2018; Oishi et al, 2017b; Qiu et al, 2012; Wang et al, 2019; Zhou et al, 2019). For example, the wake-promoting actions of caffeine (Lazarus et al, 2011) and modafinil (Qiu et al, 2012) crucially depend on their effects in the NAc.…”
Section: Introductionsupporting
confidence: 83%
“…Conversely, activation and inhibition of VTA GABA neurons was found to promote sleep and wakefulness, respectively (Chowdhury et al, 2019; Yu et al, 2019), in part due to the impact of these manipulations on the activity of VTA dopamine neurons. Because the VTA is the major source of dopaminergic innervation of the NAc, these findings are consistent with multiple additional lines of evidence implicating the NAc in the regulation of arousal and sleep (Barik and de Beaurepaire, 2005; Lazarus et al, 2011; Lena et al, 2005; Luo et al, 2018; Oishi et al, 2017b; Qiu et al, 2012; Wang et al, 2019; Zhou et al, 2019). For example, the wake-promoting actions of caffeine (Lazarus et al, 2011) and modafinil (Qiu et al, 2012) crucially depend on their effects in the NAc.…”
Section: Introductionsupporting
confidence: 83%
“…Conversely, activation and inhibition of VTA GABA neurons was found to promote sleep and wakefulness, respectively (Chowdhury et al, 2019;Yu et al, 2019), in part due to the impact of these manipulations on the activity of VTA dopamine neurons. Because the VTA is the major source of dopaminergic innervation of the NAc, these findings are consistent with multiple additional lines of evidence implicating the NAc in the regulation of (Barik and de Beaurepaire, 2005;Lazarus et al, 2011;Lena et al, 2005;Luo et al, 2018;Oishi et al, 2017b;Qiu et al, 2012;Wang et al, 2019;Zhou et al, 2019). For example, the wake-promoting actions of caffeine (Lazarus et al, 2011) and modafinil (Qiu et al, 2012) crucially depend on their effects in the NAc.…”
Section: Introductionsupporting
confidence: 80%
“…Sex-related discrepancies were consistent for the vesicular transporters Vglut1 and Vgat and their ratio (Wang et al, 2019) in the PFC, where PNS males showed increased levels of Vglut1 expression and, consequently, higher Vglut1:Vgat, than did controls, which may foster dysregulation of the prefrontal glutamatergic system. On the other hand, females did not exhibit any effect of PNS on these genes in this region.…”
Section: Discussionmentioning
confidence: 72%